A New Report on Karyological Analysis of the Jewel-Beetle, Sternocera ruficornis (Coleoptera, Buprestidae) from Thailand - Muanglen, Nawarat; Sribenja, Kamika; Chaiyasan, Pacharaporn; Tanomtong, Alongklod; Nuchjangreed, Chadaporn (Food Agricultural Sciences and Technology, 2021)
Abstract The first karyological analysis of the Jewel-Beetle, (Coleoptera, Buprestidae) was achieved by using the squash technique collected from the male gonad. Furthermore, the chromosomes were stained by conventional staining and the Ag-NOR banding techniques. The results showed the diploid number of chromosomes was 2n=26, comprising 4 metacentric, 6 submetacentric, 6 acrocentric and 8 telocentric chromosomes. The sex chromosome system was XY system with X and Y chromosomes being metacentric and acrocentric chromosomes, respectively. In addition, nucleolar organizer regions (NORs) are clearly observed near the centromere of chromosome pair one and the subcentromeric region of chromosome pair nine. The karyotype formula demonstrated as follows: 2n (26) =Lm2+Sm2+Ssm6+Sa6+St8+XY.